The Nutrition Monopoly Media Education on Knowledge, Attitudes and Fruit Vegetable Consumption in Overweight Adolescents - Amelia, Lula Putri; Srimiati, Mia; Khasanah, Tri Ardianti (Sarana Ilmu Indonesia (salnesia), 2024)
The incidence of overweight among teenagers aged 16–18 years in Indonesia increased from 1,4% in 2010 to 7,3% in 2015, with 5,7% overweight and 1,6% obese. This highlighted the growing concern of nutritional difficulties within this age group. Examining the effects of monopoly nutrition media and films on adolescent knowledge, attitudes, and fruit and vegetable intake at SMAN 1 Bojonggede was the primary goal of this project. A quasi-experimental approach with a pretest-posttest control group was used in the investigation. Thirty undergraduates participated in the study, with participants selected using stratified random selection methods. And then splitted into two groups: one to get nutrition monopoly media as an intervention and another to have video shown as a control. We took a pretest and a posttest to gauge participants’ knowledge and attitudes over the course of two weeks. The SQ-FFQ was used to collect baseline data on participants’ intake one week before the intervention and again one week after it. In one set of analyses, the Wilcoxon Test and Paired Sample T-Test were used, whereas in another set, the Mann Whitney test and Independent Sample T-Test were employed. A statistical analysis reveals that the intervention group’s knowledge is significantly different from the control group’s (p-value=0,003) and that the intervention group’s attitude is significantly different from the control group’s (p-value=0,000). Consumption of calories, carbohydrates, and fiber doesn't change significantly (p-valur >0,05).